The Analysis of Differences in Body Temperature and Blood Pressure Before and After Exposure to Hot Work Climates - Sarah Nadhila Rahma; Mahfiro Risky Safitri; Abdul Rohim Tualeka (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Working in a hot work environment has a negative impact on occupational health and safety. The impact on health due to work at temperatures above a comfortable temperature can affect body temperature and blood pressure of workers. The aim of this study was to analyze the differences in body temperature and blood pressure of workers before and after exposure to hot work climates at PT. Pertamina (Persero) Tanjung Wangi. Method: This research was an observational study with cross sectional approach. The population of this study was all workers at PT. Pertamina (Persero) Tanjung Wangi., with the total of 11 people. The sample in this study was obtained by total sampling method with a sample of 11 workers. The dependent variables in this study were body temperature, blood pressure, age, fluid intake, and nutritional status, while the independent variable was work climate. Results: Most of the grass lathe workers at PT. Pertamina (Persero) Tanjung Wangi has an age between 17-25 years, some of the grass lathe workers had a fluid intake with less categories with normal nutritional status. The measurement results showed that the average ISBB value was 28.8°C, this value still exceeded TLV. In addition, the results showed that there were differences in body temperature before and after work, from 36.04° C to 36.8° C. In addition there were differences in systolic and diastolic blood pressure before work which was 112.7 mm Hg 77.3 mm Hg, and the average after work was 121 mm Hg and 83.6 mm Hg. Conclusion: There is a difference between body temperature and blood pressure before and after exposure to hot work climates.Keywords: blood pressure, body temperature, hot work climate